2017
DOI: 10.1139/apnm-2016-0441
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of physical activity behaviours in university students enrolled in kinesiology degree programs

Abstract: Studies of physical activity behaviours have increasingly shown the importance of heritable factors such as genetic variation. Non-synonymous polymorphisms of alphaactinin 3 (ACTN3) and the β-adrenergic receptors 1 and 3 (ADRB) have been previously associated with exercise capacity and cardiometabolic health. We thus hypothesized that these polymorphisms are also related to physical activity behaviors in young adults. To test this hypothesis we examined relationships between ACTN3 (R577X), ARDB1 (Arg389Gly) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…In line with previous reviews [12,19,20] we noted that phenotype definitions of physical activity varied considerable between studies, including constructs such as walking distance [32], low-intensity physical activity [45,52], moderate intensity physical activity [34,36,49], vigorous physical activity [34,37], energy expenditure [29,31,48], engagement in sports activities [44,51], meeting Table 3 Genotype-phenotype associations in medium (6-8.5 points) and high (≥9 points) quality candidate gene studies and GWAS. For GWAS, results with a genome-wide significance level of p < 5 × 10 −8 or lower are presented.…”
Section: Discussionsupporting
confidence: 83%
“…In line with previous reviews [12,19,20] we noted that phenotype definitions of physical activity varied considerable between studies, including constructs such as walking distance [32], low-intensity physical activity [45,52], moderate intensity physical activity [34,36,49], vigorous physical activity [34,37], energy expenditure [29,31,48], engagement in sports activities [44,51], meeting Table 3 Genotype-phenotype associations in medium (6-8.5 points) and high (≥9 points) quality candidate gene studies and GWAS. For GWAS, results with a genome-wide significance level of p < 5 × 10 −8 or lower are presented.…”
Section: Discussionsupporting
confidence: 83%
“…The studies have been done on different sport disciplines and on athletes of different ethnic backgrounds, making it possible to assess the importance of ACTN3 genotypes on the performance of athletes of different backgrounds. While some studies yield expected results in terms of R allele positively correlating with an extraordinary success in strength/power disciplines and X with endurance disciplines (CHIU et al, 2011;MASSIDDA et al, 2009;PAPADIMITRIOU et al, 2016;SHANG et al, 2010), other studies are giving completely opposite results (for example, a study by MAGI et al, 2016, in which Estonian cross-country skiers were enriched in R allele, although they are performing in an endurance discipline) or did not find any correlation at all (GINEVICIENE et al, 2016;GREALY et al, 2013;MANY et al, 2016;MASSIDDA et al, 2015;YVERT et al, 2016). The present study is serving as groundwork with general population data for seven populations from the Balkan countries to which genotype frequencies from elite sportspersons can be compared in order to assess the importance of the study ACTN3 polymorphism alleles in predisposition for advantageous sport performance.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, Nirengi et al 19 reported a close association of the ACTN3 577XX genotype with higher triglyceride levels compared to the RR or RX genotypes in rugby players, and Deschamps et al 15 found differences in cardiometabolic parameters between XX and RX or RR genotype of healthy young adults and suggested a role for the ACTN3 R577X polymorphism in human metabolism. Despite the aforementioned findings, Many et al 31 did not show a significant association between ACTN3 genotypes with cardiometabolic or fitness parameters in university students.…”
Section: Discussionmentioning
confidence: 85%
“…26,30 These findings are similar to other populations where HIV+ patients carrying the ACTN3 577XX genotype had higher glucose levels and a tendency for higher serum triglyceride levels compared to patients carrying the RR or RX genotype. 20 Furthermore, Nirengi et al 19 reported a close association of the ACTN3 577XX genotype with higher triglyceride levels compared to the RR or RX genotypes in rugby players, and Deschamps et al 15 found differences in cardiometabolic parameters between XX and RX or RR genotype of healthy young adults and suggested a role for the ACTN3 R577X polymorphism in human 31 did not show a significant association between ACTN3 genotypes with cardiometabolic or fitness parameters in university students.…”
Section: Discussionmentioning
confidence: 99%